De-americanising media studies and the rise of "Chindia" - Thussu, Daya Kishan (Javnost (Ljubljana), 2013)
The creation of a global market has not only contributed to the globalisation of Western and, more specifically, American media around the world, but also opened up the media and communication sectors in large and hitherto highly regulated countries such as China and India. The resultant flow of media products from such countries has created more complex global information, infotainment and entertainment spheres. This article examines the increasing importance of China and India in global communication and media discourses and the challenge that the rise of "Chindia" poses for the study of media and communication. It argues that the globalisation of media industries and audiences, combined with the internationalisation of higher education - reflected in the changing profile of both faculty and students - requires a new approach for research and the teaching of media and communication. While global media and their study remain firmly embedded in a Western or, more accurately, American discourse, the new realities of the post-2008 world warrant a re-evaluation of how we define the global. The article concludes by considering what "Chindia" might mean in a de-Americanised media world.
Keywords: Kitajska; India; Indija; mass media; množični mediji; globalizacija; globalization